Comparison of root system and stomata in nine upland rice varieties - Raumjit, N.; Siwadon, S.; Sukanya, S.; Thirayut, W. (International Journal of Agricultural Technology, 2019)
The root system and stomata of upland rice have important implications for both nutrient uptake and drought tolerant. The drought is one of the most known limiting factors of crop cultivation during rainy season which is caused from the climatic change. The root system and stomata in nine upland rice varieties:- Pukaotong, Samduen, Lebnok, Nangdam, Dokkam, Nangkruan, Nangchuan, Lebmuenang and Dawk Pa-yawm was reported. Result found that root system and stomata were associated with drought tolerance of upland rice. Among the nine upland rice varieties, Pukaotong variety had the moderate plant height, root length, root thickness number root and number stomata. On the other hand, Pukaotong variety had the lowest length of long cell and high yield per plant, indicating the high drought tolerance ability.